Build-Operate-Transfer (BOT) Arrangements: The Experience and Policy Challenges - Adora Navarro (Philippine Institute for Development Studies (PIDS), 2005)
A look into projects under the Philippine program of public-private sector partnerships during the period 1999-2003 showed that participation of the private sector has been declining. This paper postulates that some of the reasons for dwindling investor appetite are related to contract design and implementation. It examines the nature of BOT-type contracts, their design and content and conducts a case study of a challenging BOT-type contract and identifies issues and problems faced by the government and private investors in implementing the contract. Finally the paper recommends that further amendments to the present BOT Law and its IRR must be explored to identify ways in which contractual incompleteness may be minimized. A thorough examination of the integration of law and economics in contract design as future research was also suggested.
Keywords: 330; infrastructure investments; BOT projects; public-private sector partnerships; Öffentlicher Bauauftrag; Ausschreibung; Infrastrukturinvestition; Öffentlich-private Partnerschaft; Bauwirtschaft; Philippinen